Ethics Use In Accounting Science Teaching : Study Of Phenomenology In Accounting Study Program Wijaya Kusuma Surabaya University - Kholidiah (INTELLECTUAL CAPITAL, Jurnal Akuntansi Kontemporer, 2024)
This study aims to explore and analyze the content of ethics in teaching courses in accounting sciences, namely Introduction to Accounting, Cost Accounting, Management Accounting, and Advanced Financial Accounting. The object of this research is the Accounting Study Program at the Faculty of Economics and Business, University of Wijaya Kusuma Surabaya. The subjects of this study were 8 accounting lecturers and 24 accounting students. The research approach uses a qualitative phenomenological approach by observing, interviewing, documenting and digging for other information that supports the results of this study. The results showed that based on the accounting curriculum offered, the ethical content contained in the four accounting subjects was still lacking or even there was no specific material discussing ethics.